2013
DOI: 10.1039/c3ta00682d
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral and truncated high-voltage spinel cathodes: the role of morphology and surface planes in electrochemical properties

Abstract: High-voltage spinel cathodes LiMn 1.5 Ni 0.5 O 4 are promising candidates for large-scale energy-storage applications such as electric vehicles. However, the widespread adoption of this high-voltage spinel cathode is hampered by severe capacity fade, particularly at elevated temperatures, resulting from aggressive formation of a thick solid-electrolyte interphase (SEI) layer through side reactions with the electrolyte at the high operating voltage, cationic ordering between Mn 4+ and Ni 2+ ions in the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 33 publications
2
132
0
1
Order By: Relevance
“…This embodies in the disputed results of both experimental data [26e30] and theoretical calculation [31e35]. Particularly, the results are also conflicted in high-voltage spinel LNMO system [28,30,32], because the surface behaviors with electrolyte at high operating voltage are affected by more factors like cation ordering, oxygen vacancies, size effect, and so on. Nevertheless, it is still a huge challenge to get LNMO with regular surface facets significantly improving the electrochemical performance.…”
Section: Introductionmentioning
confidence: 51%
“…This embodies in the disputed results of both experimental data [26e30] and theoretical calculation [31e35]. Particularly, the results are also conflicted in high-voltage spinel LNMO system [28,30,32], because the surface behaviors with electrolyte at high operating voltage are affected by more factors like cation ordering, oxygen vacancies, size effect, and so on. Nevertheless, it is still a huge challenge to get LNMO with regular surface facets significantly improving the electrochemical performance.…”
Section: Introductionmentioning
confidence: 51%
“…Furthermore, the cycling stability and rate capability decrease when the octahedral spinel particles are truncated. 26 The results of the chemical analysis are listed in Table S1. XRD and FTIR spectrometry are performed to identify the structural differences between the four analyzed materials (s. Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Furthermore the voltage profiles and the capacities are dependent on the synthesis temperature. [28][29][30] In this work we show the difference in the electrochemical behavior between Fe-, Ti-doped LNMO and Ru-, Ti-doped LNMO spinels.…”
mentioning
confidence: 99%
“…Doping with metal ions (Cr [15], Mg [16]) is another commonly used means for improving the cycle and rate performances of ordered LiNi 0.5 Mn 1.5 O 4 material, although it also cannot avoid the disadvantages of a complex synthesis process, increasing cost and/or reducing the discharge capacity. Recently, Manthiram [17,18] and co-workers have found that surface planes have an important effect on the electrochemical properties of ordered LiNi 0.5 Mn 1.5 O 4 cathode. Interestingly, our group [19] have also achieved a disordered LiNi 0.5 Mn 1.5 O 4 material with a good compatibility between energy/power density and cycle life without sacrificing any other properties through synthesizing a chamfered polyhedral structure.…”
Section: Introductionmentioning
confidence: 98%